2020
DOI: 10.1115/1.4046921
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Quantify Tensile Biaxial Properties of Mouse Aortic Valve Leaflets

Abstract: Understanding aortic valve (AV) mechanics is crucial in elucidating both the mechanisms that drive the manifestation of valvular diseases as well as the development of treatment modalities that target these processes. Genetically modified mouse models have provided mechanistic insight into AV development and disease. However, very little is known about mouse aortic valve leaflet (MAVL) tensile properties due to their microscopic size (~500µm long and 45µm thick) and the lack of proper mechanical testing modali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The difference in tensile properties of human and mouse AoV tissues, both healthy and diseased, remains unknown due to the small, microscopic size of mouse AoV leaflets. Recently, we developed a method to quantify equiaxial properties of mouse AoV leaflets ( 60 ), which could lead to a better understanding of the similarities between the mechanical properties of both species and how they influence sound production.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in tensile properties of human and mouse AoV tissues, both healthy and diseased, remains unknown due to the small, microscopic size of mouse AoV leaflets. Recently, we developed a method to quantify equiaxial properties of mouse AoV leaflets ( 60 ), which could lead to a better understanding of the similarities between the mechanical properties of both species and how they influence sound production.…”
Section: Discussionmentioning
confidence: 99%
“…Despite challenges with assessing small regions of interest for micromechanical testing, this is the first study to compare localized stiffness with corresponding ECM fiber patterning in freshly isolated wholemount murine AoV. Although we previously reported that unequal levels of pigmentation may occur amongst the left, right and coronary leaflets of the AoV (25), in this study all WT and K5-Edn3 leaflets that were used for biomechanical analyses were pigmented and we did not tract their anatomical position within the valve. We recognize this may have introduced some biases in the results and suggest that future studies take into consideration leaflet position to account for potential ontogenetic and histological differences among the three leaflets.…”
Section: Discussionmentioning
confidence: 99%